ETHNOSCIENCE ANALYSIS IN SCIENCE LEARNING IN PRIMARY SCHOOLS (ELEMENTARY SCHOOL) - Sukarma, I Ketut (PT. Hafasy Dwi Nawasena, 2023)
Students' awareness of Indonesian culture and traditional knowledge has declined as a result of globalization, Ethnoscience is a teaching strategy that combines conventional wisdom with contemporary ideas. It is considered an efficient teaching method, especially when it comes to teaching science in elementary schools. This research was conducted in three elementary schools located in Mataram City, West Nusa Tenggara, while the elementary schools that became the research sites were SD Negeri 15 Mataram, SD Negeri 19 Mataram, and SD Negeri 20 Mataram. The type of research used is Descriptive Qualitativ. The samples in this research are 4th and 5th grade teachers with a total of 6 teachers. The results of the study state that ethnoscience-based science learning design can be applied to several science learning materials, the application of ethnoscience-based science learning has gone well. Each school conducts evaluation activities with the aim of being a forum for teachers to convey complaints and opinions related to ethnoscience-based learning.